ACHIEVING SUSTAINABILITY AND IMPROVING GLOBAL BUSINESS PERFORMANCE THROUGH BUSINESS ETHICS AND CORPORATE SOCIAL RESPONSIBILITY: A Systematic Literature Review - Rozalina, Novianty; Ellitan, Lena (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2024)
Abstract The idea of ​​sustainable business practices and CSR has evolved over the years from simply a philanthropic endeavor to an integral component of corporate strategy. On the other hand, CSR covers a wider range of initiatives aimed at making a positive contribution to society, covering areas such as community development, employee welfare and ethical governance. This article aims to: (a). Identify relevant studies regarding the relationship between business ethics and Corporate Social Responsibility in improving global business performance and achieving sustainability. (b). Evaluate key findings from existing literature on the linkages between these practices in improving global business performance and achieving sustainability. (c). Identify research gaps that still need to be filled and recommend future research directions in this area. has an important role in international business activities. These three interrelated factors in international business play a beneficial role in ensuring that companies operate responsibly, sustainably, and provide benefits to communities and the environment around the world. Business ethics ensures that companies operate responsibly and with integrity in a complex and diverse international environment, taking into account the varying cultures, values ​​and laws of each country and region. Meanwhile, sustainable business practices are becoming increasingly important in international business due to increasing environmental and social pressures, as well as demands from consumers and governments to pay attention to the social and environmental impacts of business.